Zur Konvergenz der nationalen Raumordnungspolitiken Frankreichs und Deutschlands im Post-EUREK-Prozess: Das Subsidiaritätsprinzip in der europäischen Verfassungsvertrags-Debatte und deren Auswirkungen auf die Ausformung einer gemeinschaftlichen Raumentwicklungspolitik - David, Carl-Heinz (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The concepts of the French aménagement du territoire and of German spatial planning have approached each other in the post-EUREK-process that began after 1999. After the withdrawal of the EU-Commission from the EUREK-process that was organised intergovernmentally until then the evolved organisational and procedural structures of CEMAT and the structures that were newly created by the Commission are existing side by side. The pursuit of European spatial planning interests by the member states is strengthened by the principle of subsidiarity that is included in the European treaties. With the re-organisation of the objective- and competence system of the EU, particularly through the introduction of the aspect of “territorial cohesion” that is associated with article 16 EGV (services of general economic interest), the debate on the European Constitutional Treaty raises different questions regarding the future organisation of a European spatial development policy. At any rate the existing insecurity concerning the competence of the EU in spatial planning is not removed by the constitutional treaty. Political interests that go in the same direction can be followed more effectively within the states and on the European level through the approach of spatial planning policy.